On understanding grammar - Givón, Talmy, 1936- (John Benjamins Publishing Company, 2018)
In his foreword to the original edition of this classic of functionalism, typology and diachrony, Dwight Bolinger wrote: "I foresee it as one of the truly prizes statements of our current knowledge?a book about understanding done with deep understanding? of language and its place in Nature and in the nature of humankind? The book is rich in insights, even for those who have been with linguistics for a long time. And beginners could be thankful for having it as a starting point, from which so many past mistakes have been shed". Thoroughly revised, corrected and updated, 'On Understanding Grammar' remains, as its author intended it in 1979, a book about trying to make sense of human language and of doing linguistics. Language is considered here from multiple perspectives, intersecting with cognition and communication, typology and universals, grammaticalization, development and evolution. Within such a broad cross-disciplinary context, grammar is viewed as an automated, structured language-processing device, assembled through evolution, diachrony and use. Cross-language diversity is not arbitrary, but rather is tightly constrained and adaptively motivated, with the balance between universality and diversity mediated through development, be it evolutionary or diachronic. The book's take on language harkens back to the works of illustrious antecedents such as F. Bopp, W. von Humbold, H. Paul, A. Meillet, O. Jespersen and G. Zipf, offering a coherent alternative to the methodological and theoretical structures of Saussure, Bloomfield and Chomsky.0.